A Project report on Bio-Telementry using Mobile Phones - GOWRI, SHOBA R, SATISH KUMAR and RASHMI G P (2006)
INTENAL GUIDE : DEEPA BHANDARKAR, MVJCE EXTERNAL GUIDE: K N MARUTHY, ASSOCIATE PROFFESSOR, DEPT OF PHYSIOLOGY ST JOHNS MEDICAL COLLEGE
Keywords: Bio-Telementry using Mobile Phones